Problematika Manajemen Pendidikan di Era Digital: Tantangan dan Solusi Dalam Transformasi Pembelajaran - Sofiah Sofiah; Putri Rahmawati; Zahra Devina; Nayla Agustin A’izatun Nafisah; Davina Valencia Ernandia (JURNAL MANAJEMEN PENDIDIKAN, 2026)
Education Management Problems in the Digital Era: Challenges and Solutions in Learning Transformation Digital transformation has brought significant changes in education management, including in the context of Islamic education management. The use of digital technology offers great opportunities to improve the quality, effectiveness, and efficiency of learning, but on the other hand it also raises various complex problems. This article aims to examine the problems of Islamic education management in the digital era, especially related to challenges and solutions in learning transformation. This research uses the library research method by examining various literature sources in the form of books, journal articles, research reports, and policy documents relevant to the topic of Islamic education management and education digitalization. The results of the study show that the main challenges faced include inequality of access to technology, low readiness of human resources, and suboptimal adjustments to the curriculum and digital-based learning methods. In addition, there is still resistance to changes and limitations of digital literacy among educators and students. The solutions that can be done include the provision of adequate technological infrastructure, government policy support, the development of an adaptive digital curriculum, and continuous training for teachers and students. With the implementation of planned and integrated solutions, Islamic education management is expected to be able to adapt optimally to technological developments without ignoring Islamic values, so that learning transformation can run more effectively and sustainably.